Snuff Boxes in Lombardy (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Snuffboxes and boxes from the eighteenth-first half of the nineteenth century are very numerous and widespread in Lombardy, but little studied. To help fill this research gap, some decisive elements are analyzed here. These are letters (1770; 1774) from the correspondence of the Verri brothers, Alessandro in Rome and Pietro in Milan, relating to snuff boxes made in Milan, also in the Gaetano Grassi manufacture, and to the business that could be concluded in Rome. The document (1778) examined concerns precisely the papier-mâché box factory (a compound of paper that can be molded into molds, then fired) founded by Grassi in Milan. It is also offered a quick look at the beautiful collection of snuffboxes and boxes preserved in Brescia (Musei Civici di Arte e Storia), publishing an essay of different specimens in shape, material and decoration.
Keywords: snuffboxes; boxes; Gaetano Grassi; Milan; Brescia; Lombardy